2000
DOI: 10.1016/s0168-1591(99)00120-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term social memory in the laboratory rat: its susceptibility to disturbance

Abstract: 24 26 28 30 32 34 36 38 Adult rats presented with a juvenile conspecific for five minutes on two occasions, separated by a 15-min inter-exposure interval (IEI), investigated the reintroduced juvenile significantly less in the second encounter. It is suggested that this was because the adult rats remembered the identity of the juvenile, because when a novel juvenile was introduced for the second encounter, no such reduction in investigation was observed. When the rats were either handled, placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
2
27
2
1
Order By: Relevance
“…The current results may appear to be in conflict with other work showing that exposing an animal to a novel environment alone, impaired spatial memory in food foraging and social recognition tasks (Diamond et al 1996;Mendl 1999;Burman and Mendl 2000) and blocked the induction of hippocampal synaptic plasticity (Diamond et al 1990(Diamond et al , 1994(Diamond et al , 1999aXu et al 1997Xu et al , 1998. We suggest that differences in the effects of novelty on memory and plasticity arise from differences in the stressfulness of the training tasks.…”
Section: Figure 3 Mean ‫ע(‬ Sem) Data For Memory Errors (Rt Data Fromcontrasting
confidence: 97%
“…The current results may appear to be in conflict with other work showing that exposing an animal to a novel environment alone, impaired spatial memory in food foraging and social recognition tasks (Diamond et al 1996;Mendl 1999;Burman and Mendl 2000) and blocked the induction of hippocampal synaptic plasticity (Diamond et al 1990(Diamond et al , 1994(Diamond et al , 1999aXu et al 1997Xu et al , 1998. We suggest that differences in the effects of novelty on memory and plasticity arise from differences in the stressfulness of the training tasks.…”
Section: Figure 3 Mean ‫ע(‬ Sem) Data For Memory Errors (Rt Data Fromcontrasting
confidence: 97%
“…In rats, it has been suggested that social and individual recognition is based on olfactory cues (Gheusi et al 1994). However, memory of the identity of a conspecific in laboratory rats was reduced when a third individual was introduced between interactions (Burman and Mendl 2000). Thus, even if a species evolved the ability to recognise conspecifics individually, memory capacity may not always suffice to keep track of frequent interactions with changing partners.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that such a cage change does not disturb the social memory of Long-Evans rats [30]. Total investigation included direct investigation of the juvenile (predominantly olfactory investigation of the ano-genital area) as well as investigation of juvenile-exposed bedding.…”
Section: Methodsmentioning
confidence: 99%